THE EFFECT OF #JUMATBERKAHF EWOM AND DIMAS SETO AS SOURCE CREDIBILITY ON KAHF BRAND IMAGE - Dya Savica; Indria Angga Dianita (Business Journal : Jurnal Bisnis Dan Sosial, 2022)
The phenomenon of men who are now more aware and concerned about their selfappearance positively impacts the Indonesian men's personal care market. Therefore, this study aims to analyze the effect of eWOM and source credibility on Kahf's brand image. Through this research, it is hoped to produce an appropriate marketing strategy to build a positive brand image in the minds of consumers. This research was conducted using quantitative methods with descriptive research type. The sampling technique used in this study is probability sampling, with simple random sampling techniques. The analysis technique uses a normality test, multicollinearity test, heteroscedasticity test, coefficient correlation test, coefficient of determination, and multiple linear regression. Based on the study results, eWOM partially influenced Kahf's Brand Image by 21%, and the remaining 79% was influenced by other factors not examined in this study. Source Credibility partially influenced Kahf's Brand Image by 25%, and the remaining 75% was influenced by other factors not discussed in this study. eWOM and Source Credibility simultaneously influenced Kahf's Brand Image by 32%, and the remaining 68% was influenced by other factors not examined in this study